New insights on the impacts of e-waste towards marine bivalves: The case of the rare earth element Dysprosium. (May 2020) - Freitas, Rosa; Cardoso, Celso E.D.; Costa, Silvana; Morais, Tiago; Moleiro, Pedro; Lima, André F.D.; Soares, Márcio; Figueiredo, Samuel; Águeda, Tiago L.; Rocha, Pedro; Amador, Gonçalo; Soares, Amadeu M.V.M.; et al.
Abstract: With the technological advances and economic development, the multiplicity and wide variety of applications of electrical and electronic equipment have increased, as well as the amount of end-of-life products (waste of electrical and electronic equipment, WEEE). Accompanying their increasing application, there is an increasing risk to aquatic ecosystems and inhabiting organisms. Among the most common elements present in WEEE are rare earth elements (REE) such as Dysprosium (Dy). The present study evaluated the metabolic and oxidative stress responses of mussels Mytilus galloprovincialis exposed to an increasing range of Dy concentrations, after a 28 days experimental period. The results obtained highlighted that Dy was responsible for mussel's metabolic increase associated with glycogen expenditure, activation of antioxidant and biotransformation defences and cellular damage, with a clear loss of redox balance. Such effects may greatly impact mussel's physiological functions, including reproduction capacity and growth, with implications for population conservation. Overall the present study pointed out the need for more research on the toxic impacts resulting from these emerging pollutants, especially towards marine and estuarine invertebrate species. Graphical abstract: Image 1 Highlights: Mytilus galloprovincialis bioaccumulated Dysprosium. Mussels exposed to Dy decreased their metabolic capacity. Contaminated mussels increased antioxidant and biotransformation defences. Lipid peroxidation occurred in contaminated mussels. Oxidative stress was observed in mussels exposed to Dy. Abstract : Dysprosium induced metabolic and oxidative stress alterations in Mytilus galloprovincialis, which may impair mussels physiological mechanisms.